An advanced-time-sharing switching strategy for multiple-input buck converters - Xian, Liang (2015)
Multiple-input converter (MIC), which has higher efficiency, less component count, lower cost and simpler control method, is a promising candidate for energy harvesting in hybrid systems, and for power distribution in micro and nano grids. The principle of the proposed advanced-timesharing switching (ATSS) strategy is that the effective duty ratio of each switch is an integer multiple of a common duty ratio (CDR). CDR is the duty ratio of a common-switching-function (CSF) generated at a higher frequency by frequency division. ATSS transforms the original MIC into an equivalent single-input single-output system, simplifying system analysis, control design and implementation, where CDR is the only control variable for output voltage regulation. Additionally, multiplied by a regulation coefficient a, the fixed CDRs can become the control variables for current limitation, which releases the degree of freedom. By using this technique, smooth and accurate limitation to sources' current is able to be implemented without loss of output-voltage-regulation convenience. Its corresponding circuit modeling, small-signal analysis, controller design, and performance tests have been put forward.